Fast Facts: Brain Tumors - Abrey, Lauren E; Mason, Warren P (S. Karger, 2011)
Despite the availability of many effective treatments, there remains a therapeutic nihilism associated with brain tumors. This highly readable second edition of 'Fast Facts: Brain Tumors' challenges this view, starting from the premise that patients with brain tumors can truly benefit from a thoughtful multidisciplinary approach.This comprehensive handbook covers all the salient features of the various brain tumors and treatment modalities in a way that will be useful to the practicing clinician.• Advances in radiology and pathology that have led to more precise and detailed diagnoses• Developments in molecular biology and imaging techniques that have improved available diagnostic modalities• New neurosurgical techniques that have enabled operations on tumors that were previously considered inoperable• Novel delivery systems that allow various treatments to reach tumors that are otherwise protected by the blood-brain barrier.This fully updated edition of 'Fast Facts: Brain Tumors' bridges the gap between primary care providers - whose role is pivotal in tumor detection and subsequent patient care - and first-level specialists such as general neurologists and neurosurgeons. Its key message is that selection of the best initial approach for an individual patient will result in the best overall outcome, both in terms of survival and quality of life.'Fast Facts: Brain Tumors' is specifically for the primary care physician whose role is pivotal in tumor detection and subsequent patient care.Contents:• Classification and epidemiology• Diagnosis• Treatment• Brain metastases• Gliomas• Meningiomas• Neuronal tumors• Pineal region tumors• Skull base tumors• Primary central nervous system lymphoma• Brain tumor syndromes and tumor-like cysts• Geriatric neuro-oncology• Useful resources
Keywords: Brain Neoplasms; nádory mozku; neurologie; onkologie; Neurology